Bacteria isolated from the stools of Alzheimer's disease patients exacerbate cognitive impairment in a 3xTg AD mouse model. (1st February 2022) - Chevalier, Claire; Marizzoni, Moira; Tournier, Benjamin; Paquis, Arthur; Mirabelli, Peppino; Salvatore, Marco; Millet, Philippe; Cattaneo, Annamaria; Frisoni, Giovanni B
Abstract: Background: Human microbiota‐associated (HMA) murine models are developed by gavaging mice with human bacteria or stools and are increasingly used to study the relation between the human microbiota and disease. The aim of this study is to evaluate the effect of gut bacteria isolated from donors with or without Alzheimer's dementia on behavior in AD transgenic (Tg) mice. Method: Sixty female, one‐year old 3xTg mice (APP SWE, PS1 M146V and Tau P301L ) received (1) antibiotic treatment for 14 days before first gavage, (2) stomach acid suppressant, (3) laxative immediately before the first gavage and, (4) microbiota transplantation or saline, once every 2 weeks for 2 months. The transplanted microbiota consisted of bacteria isolated from stools of donors pertaining to four different profiles: i) an amyloid positive AD patient, ii) an amyloid negative cognitively healthy subjects with or iii) without protective APOE genotype and, iv) a young healthy donor. As additional control, we included a group of mice that received bacteria isolated from stools of untreated 3xTg mice. Stools collection and behavioral assessment (open‐field test, Y‐maze test, radial maze test, elevated plus maze test) was performed before antibiotic treatment and at day 3, 30, 60 after the first gavage. All mice were sacrificed at day 60 for ex‐vivo assessments. Result: After 60 days from first gavage, bacteria from the AD patient (i) induced AD‐like behavior in 3xTg mice, including impaired general activity in the open‐field test and exacerbated anxiety in the elevated plus maze test, compared with mice that received saline or bacteria from untreated 3xTg mice. Interestingly, bacteria from donor resilient to AD pathology (donor of profile ii) induced better cognitive score to object recognition when transplanted to 3xTg mice. Conclusion: The microbiota of AD patients induced an AD‐like phenotype in 3xTg mice, and microbiota from patient resilient to AD pathology induced a better memory score. Brain and gut ex‐vivo assessments, 16S rRNA gene sequencing as well as behavioral longitudinal analysis are on‐going to evaluate the human microbiota transplantation efficiency and its effect on AD pathology and inflammation.